Hubungan Usia dan Paritas Terhadap Kejadian Pre Eklampsia di RSD Balung Jember - Yuningsih (ARTERI : Jurnal Ilmu Kesehatan, 2021)
One of the contributors to maternal and infant mortality is the incidence of preeclampsia that occurs during pregnancy. The cause of preeclampsia is still unknown, but it is suspected that age and parity are one of the triggers for this occurrence. Women of childbearing age who are nulliparous with extreme age under the age of less than 20 years and women with the age of more than 35 years are most commonly found to have preeclampsia. The design in this study is analytic with a cross sectional approach. The population of all mothers giving birth in the delivery room of RSD Balung Jember was 3594 in 2019. The number of samples taken using non-random sampling by purposive sampling was finally obtained by 97 respondents. In this study, the independent variables were maternal age and parity, while the dependent variable was the incidence of preeclampsia. The instrument used is medical records. The data is processed by editing, coding, processing and cleaning processes. Data were analyzed using multiple logistic regression. The results of the chi-square test for the age variable obtained that the Pearson chi-square value was 0.019 and the p value = 0.000 <0.05 from these results Ho was rejected, and the parity variable the Pearson chi-square value was 0.019 and the p value = 0.000 <0.05 from these results Ho is rejected. In conclusion, there is a relationship between age and preeclampsia, and there is a relationship between parity and preeclampsia.